2018
DOI: 10.3390/mti2030037
|View full text |Cite
|
Sign up to set email alerts
|

What Characterizes the Polymodal Media of the Mobile Phone? The Multiple Media within the World’s Most Popular Medium

Abstract: While the mobile phone is the world's most popular media device, it is actually not one single medium, but is effectively used as a different medium by different user groups. The article characterizes polymodal differences in mobile apps usage among different user groups, including gender, education, occupation, screen size, and price. We monitored the complete app usage of 10,725 smartphone users for one month each (56 million sessions, recording almost 1 million hours). Our key contribution consists in devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…To narrow down the design space, we followed three primary design principles as heuristics, however other indirectly related factors (e.g., user body motion) were considered: C1 -Design for small screen displays. Considering the small screen size of mobile devices (typically 3-6" [46,90,111]), the design should be as simple as possible to minimize distraction on video watching. Furthermore, it should account for the fat finger problem [94] so as not to occlude neither the content nor the annotation interface.…”
Section: Designing Our Mobile Annotation Methodsmentioning
confidence: 99%
“…To narrow down the design space, we followed three primary design principles as heuristics, however other indirectly related factors (e.g., user body motion) were considered: C1 -Design for small screen displays. Considering the small screen size of mobile devices (typically 3-6" [46,90,111]), the design should be as simple as possible to minimize distraction on video watching. Furthermore, it should account for the fat finger problem [94] so as not to occlude neither the content nor the annotation interface.…”
Section: Designing Our Mobile Annotation Methodsmentioning
confidence: 99%
“…While Elliott et al (2020) indicated no effect on reading speed, Hsieh et al (2016) reported that individuals read faster on smaller screens. Hilbert and Aravindakshan (2018) showed that larger screens were associated with more extensive sessions, while smaller screens were associated with more frequent intensive use. Moreover, current mobile web pages and apps have far greater usability than in the past (Kortum & Sorber, 2015).…”
Section: Presumption Of Pc Superiority and Mobile Inferioritymentioning
confidence: 98%
“…Adepu and Adler (2016) and Sundar et al (2018) argue that haptics, specifically touchscreens, and voice input and transcription, allow for many additional benefits for mobile usage and can provide improved accessibility. The integration of a camera, Internet, screen, keyboard, microphone, and Global Positioning System (GPS) allows for many activities, including content creation, promotion, distribution, and consumption, to be done more easily on smartphones than with PCs (Hilbert & Aravindakshan, 2018; Schrock, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%